2011
DOI: 10.17221/1435-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for linear type traits in Czech Holstein cattle

Abstract: A primary reason for collecting and utilizing information on type is to aid breeders in selecting profitable, functional cows in order that early culling for causes unrelated to yield (involuntary culling) can be avoided (Misztal et al., 1992). Selection on yield traits alone could decrease merit for traits with antagonistic genetic correlations with yield. Selection emphasis on type traits associated with increased herd life may be beneficial to decrease involuntary culling and increase profitability (Rogers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
26
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 16 publications
16
26
2
1
Order By: Relevance
“…The estimates of heritabilities of leg traits were consistent with those reported by Ptak et al (2011) and Zavadilova and Stipkova (2012), and lower than obtained by Misztal et al (1992), Berry et al (2004), Lassen and Mark (2008), and Nemcova et al (2011). All those results confirm that leg traits are strongly influenced by environmental conditions and rather difficult to improve by selection.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The estimates of heritabilities of leg traits were consistent with those reported by Ptak et al (2011) and Zavadilova and Stipkova (2012), and lower than obtained by Misztal et al (1992), Berry et al (2004), Lassen and Mark (2008), and Nemcova et al (2011). All those results confirm that leg traits are strongly influenced by environmental conditions and rather difficult to improve by selection.…”
Section: Resultssupporting
confidence: 89%
“…All those results confirm that leg traits are strongly influenced by environmental conditions and rather difficult to improve by selection. The estimates of heritabilities for udder traits were very close to those reported by Berry et al (2004) and Zavadilova and Stipkova (2012) but lower than those obtained by Lassen and Mark (2008) and Nemcova et al (2011). Berry et al (2004) reported higher heritability for chest width (0.26) and much higher for body depth (0.37).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The posterior mean of heritability for linear type traits obtained in conjunction with each measure of longevity (Long1_60, Long1_72, Long2_48 and Long2_54) showed low variation, which for the most part were 0.01 and 0.02 points, except for stature (0.04) and body depth, rump angle, foot angle and udder cleft that showed variation of 0.03 (Table 4). Low heritabilities for hoof angle (0.10) and udder texture (0.11) were also observed by Campos et al (2012) in Holstein cows, as well as by Němcová et al (2011) and Lagrotta et al (2010) in Holstein and Gir cattle, respectively, for hoof angle (0.09 and 0.12). The posterior residual correlations were low, ranging from -0.05 to 0.09 (Table 5).…”
Section: Resultsmentioning
confidence: 93%